Vzpostavitev podpornega odnosa v superviziji s poudarkom na empatiji - Ščavničar, Ema (Obzornik zdravstvene nege, 2003)
Helping relationship between client and supervisor is building during the process of supervision. It must be client centered. In the article has been introduced some theoretical models, which are necessary to the supervisor who leads the process. Particular accent has been given to the empathy which is a way of being with the client and is expressed in action.
Keywords: Empathy; Empatija; health care; Interpersonal Relations; medicinske sestre; Medosebni odnosi; Nega bolnika, nadzor; Nursing, Supervisory; supervizija; zdravstvo